Contemporary Approaches to Modulating the Nitric Oxide–cGMP Pathway in Cardiovascular Disease. Issue 7 (31st March 2017) - Kraehling, Jan R.; Sessa, William C.
Abstract : Endothelial cells lining the vessel wall control important aspects of vascular homeostasis. In particular, the production of endothelium-derived nitric oxide and activation of soluble guanylate cyclase promotes endothelial quiescence and governs vasomotor function and proportional remodeling of blood vessels. Here, we discuss novel approaches to improve endothelial nitric oxide generation and preserve its bioavailability. We also discuss therapeutic opportunities aimed at activation of soluble guanylate cyclase for multiple cardiovascular indications.